2017
DOI: 10.1136/bmjopen-2017-017521
|View full text |Cite
|
Sign up to set email alerts
|

Can physical assessment techniques aid diagnosis in people with chronic fatigue syndrome/myalgic encephalomyelitis? A diagnostic accuracy study

Abstract: ObjectiveTo assess five physical signs to see whether they can assist in the screening of patients with chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) and potentially lead to quicker treatment.MethodsThis was a diagnostic accuracy study with inter-rater agreement assessment. Participants recruited from two National Health Service hospitals, local CFS/ME support groups and the community were examined by three practitioners on the same day in a randomised order. Two allied health professionals (AHPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
2
29
0
4
Order By: Relevance
“…Post-mortem SARS research indicated the virus had crossed the blood brain barrier into the hypothalamus via the olfactory pathway [2]. The pathway of the virus seemed to follow that previously suggested in CFS/ME patients, involving disturbance of lymphatic drainage from the microglia in the brain [3].One of the main pathways of the lymphatic drainage of the brain is via the perivascular spaces along the olfactory nerves through the cribriform plate into the nasal mucosa [4]. If the pathogenesis of coronavirus affects a similar pathway, it could explain the anosmia observed in a proportion of COVID-19 patients.…”
Section: Letter To the Editormentioning
confidence: 65%
See 2 more Smart Citations
“…Post-mortem SARS research indicated the virus had crossed the blood brain barrier into the hypothalamus via the olfactory pathway [2]. The pathway of the virus seemed to follow that previously suggested in CFS/ME patients, involving disturbance of lymphatic drainage from the microglia in the brain [3].One of the main pathways of the lymphatic drainage of the brain is via the perivascular spaces along the olfactory nerves through the cribriform plate into the nasal mucosa [4]. If the pathogenesis of coronavirus affects a similar pathway, it could explain the anosmia observed in a proportion of COVID-19 patients.…”
Section: Letter To the Editormentioning
confidence: 65%
“…This disturbance leads to a build-up of pro-inflammatory agents, especially post-infectious cytokines such as interferon gamma, and interleukin 7 [5], which have been hypothesized to affect the neurological control of the 'Glymphatic System' as observed in CFS/ME [3]. The build up of cytokines in the Central Nervous System (CNS) may lead to post viral symptoms due to pro-inflammatory cytokines passing through the blood brain barrier in circumventricular organs such as the hypothalamus, leading to autonomic dysfunction manifesting acutely as a high fever and in the longer term to dysregulation of the sleep/wake cycle, cognitive dysfunction and profound unremitting anergia, all characteristic of CFS/ME.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on the coronavirus and the influenza virus epidemics have suggested that these agents can alter the immune response. Moreover, the pro-inflammatory cytokines such as interferon-gamma and interleukins are released following the viral infection, passing through the blood-brain barrier and affecting the central nervous system (CNS) organs such as the hypothalamus (Hives et al 2017 ). The autonomic alteration consequence of hypothalamus involvement may result in cognitive abnormality, sleep/wake cycle dysregulation, profound fatigue, and myalgia in the long term in favor of CSF/ME (Carruthers et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that ME/CFS can be treated using the Perrin technique, based on traditional osteopathic concepts, to restore a healthier neuro-lymphatic flow. The Perrin technique is a system of manual diagnosis and treatment that is based on the hypothesis that ME/CFS is a disorder of the lymphatic drainage of the CNS, which leads to five physical signs [39] . I further postulate that patients with post-COVID-19 fatigue syndrome may also benefit from CSF drainage in the same way as CFS patients do [26] , [27] , [28] .…”
Section: Discussionmentioning
confidence: 99%